Херсонеський музей очима відвідувачів - Діанова, Т.В.; Красовська, Н.В. (Інститут археології НАН України, 2009)
Висвітлено маловідомі сторінки історії Херсонеського музею, які відкриває Книга відвідувачів цього музею. Херсонесский музей, основанный в 1892 г., является одним из старейших музеев Украины. Формирование архива музея началось в 1888 г. Благодаря тому, что его одним из первых эвакуировали в годы Первой и Второй мировых войн, а также самоотверженности его сотрудников удалось сохранить значительную часть документов. В статье использованы документы лишь одного периода истории Херсонесского музея — с момента основания в 1892 г. до середины 1940-х гг. Из анализа только одной категории архивных документов — Книг посетителей — можно сделать вывод, что с момента основания музей пользовался большой популярностью среди самых различных категорий населения, о чем свидетельствует неуклонный рост численности его посетителей. Established in 1892, the museum in Chersonesos is one of the oldest museums in Ukraine. Museum archive has been formed since 1888. In the ages of the World War ІІ, a great part of the documents were saved by the exertion of the museum staff and due to the fact that it was one of the first museums that left for the evacuation. The given paper analyses the documents from a single period in the history of the museum in Chersonesos: from 1892, when the museum was founded, to the mid. 1940s. The analysis of a single category of archival documents, visitors’ books, allows one to draw the conclusion that, from its foundation date onwards, the museum was very popular among various groups of people and that the increasing number of visitors testifies that.